Persepsi Mahasiswa Ekonomi Syariah terhadap Pembelajaran Bahasa Arab di UIN Sunan Kalijaga Yogyakarta - Meiliyati, Ruhamauliyah (Study Program of Arabic Language Teaching, 2022)
Perception is the process of understanding oneself, assessing, responding, and interpreting information or stimuli from the surrounding environment that are received through the senses. This research was conducted in the Islamic Economics Research Project of UIN Sunan Kalijaga Yogyakarta. This study aims to obtain data related to the perceptions of Islamic Economics students at UIN Sunan Kalijaga towards learning Arabic and to find out the reasons for the differences in perceptions they have. This research is included in the category of case study research (field study). The approach used in this research is a descriptive qualitative approach. Where the research data is in the form of observations and questionnaires obtained from the object of research in the field. The results of this study are expected to be used as material for evaluation and consideration by lecturers who support Arabic courses, especially Sharia Economics Study Program in teaching Arabic.